Woreda-Level crop production rankings in Ethiopia: A pooled data approach - Warner, James; Stehulak, Tim; Kasa, Leulsegged (International Food Policy Research Institute, 2015)
A detailed understanding of farm production at the woreda-level is essential to plan and evaluate interventions because many agricultural policy decisions are implemented at this level. Unfortunately, there are no nationally representative woreda-level agricultural production statistics in Ethiopia. Even though the largest Ethiopian agricultural data survey, the Agricultural Sample Survey (AgSS), interviews approximately 40,000 agricultural households annually, the sampling frame is designed for zonal level, not woreda-level production estimates. We re-weight four years of the AgSS data (2010-2013) to provide woreda production rankings in the four main agricultural regions of Ethiopia (Amhara, Tigray, Oromia and the SNNP) for eight staple crops (wheat, maize, barley, sorghum, teff, chickpea, sesame, and coffee).